Life Cycle Costing of Alternative Value Chains of Biomass Energy for Cooking in Kenya and Tanzania - Okoko, Abigael; von Dach, Susanne Wymann; Reinhard, Juergen; Kiteme, Boniface; Owuor, Samuel (Journal of Renewable Energy, 2018)
In near future, wood-based biomass energy will remain the main cooking energy for households in East Africa, especially for poor households due to its availability and affordability. Alternative biomass fuels however exist. Economic viability of these alternatives is important due to its potential to influence their adoption and sustained use. This research evaluates the economic efficiency of firewood, charcoal, biogas, jatropha oil, and crop residue briquettes value chains in the rural-urban contexts of Kitui, Kenya, and Moshi, Tanzania, using Life Cycle Costing (LCC) methodology. LCC helps to identify areas along the value chains where costs occur and where improvements are feasible. Jatropha oil manual value chain has the highest cost. Firewood use with improved cook stoves is cost efficient. In Moshi’s rural context, royalty fees increases cost of charcoal. Similarly, biogas in Kitui is less likely to be economically viable. Briquettes however have a competitive advantage over charcoal. The costs are dominated by fuel provision compared to cost of stoves. Therefore, payment schemes that improve adoption of improved stoves perceived as expensive will substantially reduce fuel cost. Enhancing availability and accessibility of technologies such as briquette presses will enhance biomass energy access and provide a source of income for households.